Copper-related toxicity in replicating and dormant Mycobacterium tuberculosis caused by 1-hydroxy-5-R-pyridine-2(1H)-thiones. Issue 7 (27th June 2018) - Salina, Elena G.; Huszár, Stanislav; Zemanová, Júlia; Keruchenko, Jan; Riabova, Olga; Kazakova, Elena; Grigorov, Artyom; Azhikina, Tatyana; Kaprelyants, Arseny; Mikušová, Katarína; Makarov, Vadim
Abstract : 1-Hydroxy-5- R -pyridine-2(1 H )-thiones are novel copper-dependent M. tuberculosis inhibitors that provide intracellular accumulation of toxic concentrations of copper. Abstract : With the emerging primary resistance of Mycobacterium tuberculosis to current drugs and wide distribution of latent tuberculosis infection, the need for new compounds with a novel mode of action is growing. Copper-mediated innate immunity and its antibacterial toxicity pose novel strategies for tuberculosis drug discovery and development. Transcriptome response to 1-hydroxy-5- R -pyridine-2(1 H )-thiones, which were found to be highly active in vitro against actively growing and dormant nonculturable M. tuberculosis, revealed signs of copper toxicity. 1-Hydroxy-5- R -pyridine-2(1 H )-thiones were found to form stable charged lipophilic complexes with Cu 2+ ions that could transport into mycobacterial cells. Copper accumulated inside treated bacilli as subsequent metabolic destruction of the complex led to chemical transformation of 1-hydroxy-5- R -pyridine-2(1 H )-thiones and release of free Cu 2+ into the cytoplasm. 1-Hydroxy-5- R -pyridine-2(1 H )-thiones are a potent class of Cu-dependent inhibitors of M. tuberculosis, and may control infection by impairment of copper homeostasis.